A review of research on transformational leadership - Ming, Dai; Yuet, Fanny Kho Chee (Journal of Islamic, Social, Economics and Development, 2026)
Transformational leadership originated in the late 1970s and has since become one of the most prominent leadership styles and a major topic of research in the field of management. Existing studies have actively examined the multifaceted impacts of transformational leadership on both organizational and employee outcomes, particularly in the context of organizational change management. These studies collectively demonstrate the critical role of transformational leadership in management practice. Building on prior scholarly work, this article reviews and synthesizes the theoretical origins, structural dimensions, and practical development of transformational leadership, offering insights and references for future research.